Acute Effects of High Intensity, Resistance, or Combined Protocol on the Increase of Level of Neurotrophic Factors in Physically Inactive Overweight Adults: The BrainFit Study - Domínguez-Sanchéz, María A.; Bustos-Cruz, Rosa H.; Velasco-Orjuela, Gina P.; Quintero, Andrea P.; Tordecilla-Sanders, Alejandra; Correa-Bautista, Jorge E.; Triana-Reina, Héctor R.; García-Hermoso, Antonio; González-Ruíz, Katherine; Peña-Guzmán, Carlos A.; Hernández, Enrique; Peña-Ibagon, Jhonatan C.; et al. (Frontiers in Physiology, 2018)
The purpose of this study was to compare the neurotrophic factor response following one session of high-intensity exercise, resistance training or both in a cohort of physically inactive overweight adults aged 18–30 years old. A randomized, parallel-group clinical trial of fifty-one men (23.6±3.5 years; 83.5±7.8 kg; 28.0±1.9 kg/m2) who are physically inactive (i.e., <150 min of moderate-intensity exercise per week or IPAQ score of < 600 MET min/week for greater than 6 months) and are either abdominally obese (waist circumference ≥ 90 cm) or have a body mass index, BMI ≥ 25 and ≤ 30 kg/m2 were randomized to the following four exercise protocols: high-intensity exercise (4×4 min intervals at 85–95% maximum heart rate [HRmax] interspersed with 4 min of recovery at 75–85% HRmax) (n=14), resistance training (12 to 15 repetitions per set, at 50 to 70% of one repetition maximum with 60 s of recovery) (n=12), combined high-intensity and resistance exercise (n=13), or non-exercising control (n=12). The plasma levels of neurotrophin-3 (NT-3), neurotrophin-4 (also known as neurotrophin 4/5; NT-4 or NT-4/5), and brain-derived neurotrophic factor (BDNF) were determined before (pre-exercise) and 1-min post-exercise for each protocol session. Resistance training induced significant increases in BDNF (+15.5 ng/mL [95% CI, 1.2 to 32.3; p=0.066], NT-3 (+39.6 ng/mL [95% CI, 2.5 to 76.6; p=0.004], and NT-4/5 (+1.3 ng/mL [95% CI, 0.3 to 2.3; p=0.014]), respectively. Additionally, combined training results in favorable effects on BDNF (+22.0, 95% CI, 2.6 to 41.5; p=0.029) and NT-3 (+32.9 ng/mL [95% CI, 12.3 to 53.4; p=0.004]), respectively. The regression analysis revealed a significant positive relationship between changes in BDNF levels and changes in NT-4/5 levels from baseline to immediate post-exercise in the combined training group (R2=0.345, p=0.034) but not the other intervention groups. The findings indicate that acute HIIT, resistance training and combined exercise increase neurotrophic factors in physically inactive overweight adults. Further studies are required to determine the biological importance of changes in neurotrophic responses in overweight men and chronic effects of these exercise protocols.